La imposición al consumo en la era de los servicios digitales - Sotomayor Hernández, Pablo (2019)
Nowadays, technological development has encouraged the evolution of the international market for services and consumer goods, with respect to internal tax regulations of several states. Online non-physical services generate a gap that is not strictly addressed by the states in the provisions of their tax regulations for digital service companies. The authors analyze the current situation and challenges faced by non-domiciled digital companies when providing their main services. They observe, as well, the various aspects that should be taken into consideration in the applicable Peruvian legal framework. Moreover, providing an accurate comparison, they address the imposition to digital platforms in different countries to reach a consensus on its ideal application in Peru.